A new multi-proxy record of environmental change over the last 1000 years on Chiloé Island: Lake Pastahué, south-central Chile (42°S). (March 2019) - Troncoso Castro, J Max; Vergara, Carolina; Alvarez, Denisse; Díaz, Gustavo; Fierro, Pablo; Araneda, Alberto; Torrejón, Fernando; Rondanelli, Mauricio; Fagel, Nathalie; Urrutia, Roberto
Knowledge of past environmental and climatic conditions of lake ecosystems on Chiloé Island on a millennial scale is limited. Hence, this study fills a gap in our understanding of this part of southern Chile. The aim of this study was to reconstruct the environmental and climatic history of the last 1000 years of Lake Pastahué through a multi-proxy sediment core analysis. The 1-m-long core was subsampled every centimeter for the organic matter, magnetic susceptibility, grain-size distribution, and biological indicator (pollen, chironomids) analyses. The age model was constructed from 210 Pb, 137 Cs, and 14 C activity. Pollen results revealed a North Patagonian forest composition represented by Nothofagus, Weinmannia, Drimys, Tepualia, Myrtaceae, Poaceae, and Pteridophyta. The abundance of Rumex and Pinus in the most recent part of the pollen assemblage reflects a clear anthropogenic impact. The sedimentological parameters and chironomid assemblage show similar variations, which highlight changes in the trophic state of the lake. The changes observed in all proxies suggest the influence of climate events such as the 'Medieval Climate Anomaly' (MCA) and 'Little Ice Age' (LIA). The variations observed since the beginning of the 20th century could be the result of the combined effect of anthropogenic activities and the increase in temperature recorded in south-central Chile and Patagonia.